Youth adversity and trajectories of depression/anxiety symptoms in adolescence in the context of intersectionality in the United Kingdom - Havers, L; Shuai, R; Fonagy, P; Fazel, M; Morgan, C; Fancourt, D; McCrone, P; Smuk, M; Bhui, KS; Shakoor, S; Hosang, GM (Cambridge University Press, 2024)
Background Youth adversity is associated with persistence of depression and anxiety symptoms. This association may be greater for disadvantaged societal groups (such as females) compared with advantaged groups (e.g. males). Given that persistent symptoms are observed across a range of disadvantaged, minoritized, and neurodivergent groups (e.g. low compared with high socio-economic status [SES]), the intersection of individual characteristics may be an important moderator of inequality. Methods Data from HeadStart Cornwall (N = 4441) was used to assess the effect of youth adversity on combined symptoms of depression and anxiety (Strengths and Difficulties Questionnaire emotional problems subscale) measured at three time-points in 11–14-year-olds. Latent trajectories and regressions were estimated for eight intersectionality profiles (based on gender, SES, and hyperactivity/inattention), and moderating effects of the individual characteristics and their intersections were estimated. Results Youth adversity was associated with higher average depression/anxiety symptoms at baseline (11–12-years) across all intersectionality profiles. The magnitude of effects differed across profiles, with suggestive evidence for a moderating effect of youth adversity on change over time in depression/anxiety symptoms attributable to the intersection between (i) gender and SES; and (ii) gender, SES, and hyperactivity/inattention. Conclusions The detrimental effects of youth adversity pervade across intersectionality profiles. The extent to which these effects are moderated by intersectionality is discussed in terms of operational factors. The current results provide a platform for further research, which is needed to determine the importance of intersectionality as a moderator of youth adversity on the development of depression and anxiety symptoms in adolescence.